Study of pd-au/c nanocatalysts synthesized by underpotential deposition of cu and pd redox replacement - Yeo, Cheng Yao. (2010)
Direct formic acid fuel cells are gaining popularity due to its efficiency and safety. Palladium (Pd) based catalysts exhibit better activity towards formic acid oxidation (FAO) compared to Platinum (Pt). Thus, a study on FAO exhibited by different surface coverage of Pd on gold (Au) substrate was done. As underpotential deposition (UPD) can synthesize catalysts with specific surface coverage, it is utilised to create the Pd-Au catalyst. However, as UPD could occur over a range of values, the effect of varying the potential in the UPD range on the Cu adlayer surface coverage of gold substrate was first studied. After which, UPD, together with redox replacement, was used to synthesize the Pd-Au catalysts. Lastly, the activity of the Pd-Au catalysts on FAO was studied. The results showed that the Pd-Au catalyst with lower surface coverage possess the highest specific activity. However, they were the least stable, as their activity decreased rapidly due to electro dissolution of Pd metal into the acidic electrolyte.